MATHEMATICAL MODELING, ANALYSIS AND OPTIMAL CONTROL OF AN ALCOHOL DRINKING MODEL WITH LIVER COMPLICATION. (2020) - KHAJJI, BOUCHAIB; KOUIDERE, ABDELFATAH; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available